Magnesium and reproductive health - N V Artymuk; O A Tachkova; V O Chervov (IP Berlin A.V., 2016)
A review of published data which demonstrates the importance of magnesium deficiency in the formation of reproductive health in women and opportunities the use of magnesium preparations in medical practice, including obstetrics and gynecology.